Corporate Social Responsibility Expenditure (CSR): An Analysis of Public Sector Banks in India - Yuvika Midha, Mandeep Kaur (International Journal of Advanced Science and Technology, 2020)
This paper aims to compare the CSR expenditure made by top ten banks of public sector in India in the financial years 2015-16, 2016-17, 2017-18 and to study the association between CSR expenditure, age of the bank, net profits and net NPA ratio